Scurvy-scorbutic siderosis of gingiva: A diagnostic challenge - A rare case report - Japatti, Sharanabasappa R. (Medknow Publications & Media Pvt Ltd, 2013)
This case reports a rare condition of scurvy which posed a diagnostic difficulty. However, a thorough medical and diet history, along with clinical and histopathological examination aided in prompt diagnosis and successful management of the case. Occurrence of scurvy in today's contemporary society is said to be rare. Lack of fresh fruits and vegetables in the diet can lead to this condition. Diagnosis may be difficult due to its rarity and presence of non specific symptoms, which may pose a challenge to the clinician. A comprehensive history, clinical examination along with clinical and histopathological features led to arrive at a proper diagnosis. Local procedures and systemic therapy aided in the successful management of the case. A marked improvement in the gingival status and in the physical well being of the patient resulted after treatment. This case report describes the various manifestations of scurvy that posed a diagnostic challenge to the clinician. This condition which can be fatal if untreated can be easily prevented with inclusion of healthy food in the diet and modification in the lifestyle.